2022
DOI: 10.1038/s41598-022-11843-z
|View full text |Cite
|
Sign up to set email alerts
|

Translational development of a tumor junction opening technology

Abstract: Our goal is to overcome treatment resistance in ovarian cancer patients which occurs in most cases after an initial positive response to chemotherapy. A central resistance mechanism is the maintenance of desmoglein-2 (DSG2) positive tight junctions between malignant cells that prevents drug penetration into the tumor. We have generated JO4, a recombinant protein that binds to DSG2 resulting in the transient opening of junctions in epithelial tumors. Here we present studies toward the clinical translation of c-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Furthermore, in the context of Investigational New Drug–enabling NHP studies with a modified recombinant Ad3 fiber knob (aka JO4) that also targets DSG2, we showed that DSG2 in normal epithelial tissues, which display a strict apical basal polarization, is trapped in lateral junctions and not accessible to IV injected ligands. 10, 53 This would imply that our DSG2-targeting HDAd5/3+ vectors would be safer compared with HDAd5/35++ vectors that target the ubiquitously expressed CD46 receptor. Furthermore, in contrast to HDAd5/35++ vectors, the use of HDAd5/3+ vectors would allow for adequate toxicology studies in NHPs, a prerequisite for the clinical translation of our approach for the treatment of nonmalignant diseases such as hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the context of Investigational New Drug–enabling NHP studies with a modified recombinant Ad3 fiber knob (aka JO4) that also targets DSG2, we showed that DSG2 in normal epithelial tissues, which display a strict apical basal polarization, is trapped in lateral junctions and not accessible to IV injected ligands. 10, 53 This would imply that our DSG2-targeting HDAd5/3+ vectors would be safer compared with HDAd5/35++ vectors that target the ubiquitously expressed CD46 receptor. Furthermore, in contrast to HDAd5/35++ vectors, the use of HDAd5/3+ vectors would allow for adequate toxicology studies in NHPs, a prerequisite for the clinical translation of our approach for the treatment of nonmalignant diseases such as hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%